Peer-regarding fairness in supply chain. Issue 10 (19th May 2018) - Du, Shaofu; Wei, Lin; Zhu, Yangguang; Nie, Tengfei
Abstract: People exhibit peer-regarding fairness concern when others who are in similar circumstances are treated unfairly. The fairness concern derives from a sense of sympathy or schadenfreude. We study it in a distribution channel where a supplier deals with two retailers located at independent markets. Sympathy means the decrease of the retailer's utility because he believes that his peer's unfair treatment is undeserved, while schadenfreude indicates the utility increase as the unfair treatment is perceived deserved. The two retailers are offered wholesale prices sequentially and set their retail prices if they accept the offers. In our paper, the second retailer has the peer-regarding fairness concern. We show the following in regards to this idea: (i) the retailers' profits and the distribution channel performance can be improved by the peer-regarding fairness concern for sympathy; (ii) the retailers' profits and the channel performance can be reduced by the peer-regarding fairness concern for schadenfreude; and (iii) the peer-regarding fairness concern for sympathy is unfavourable to the supplier, and the second retailer may be punished separately if the concern is not strong enough, while the supplier benefits from the peer-regarding fairness concern for schadenfreude and may exploit the second retailer solely if the schadenfreude parameter is large.